A cohort study of diabetic patients and diabetic foot ulceration patients in China. Issue 2 (March 2015) - Jiang, Yufeng; Wang, Xuemei; Xia, Lei; Fu, Xiaobing; Xu, Zhangrong; Ran, Xingwu; Yan, Li; Li, Qiu; Mo, Zhaohui; Yan, Zhaoli; Ji, Qiuhe; Li, Qiang
ABSTRACT To determine the annual incidence and clinically relevant risk factors for foot ulceration in a large cohort study of diabetic foot ulcer (DFU) patients and diabetes mellitus (DM) patients in China. To investigate a cohort of 1, 333 patients comprising 452 DFU patients and 881 DM patients, who underwent foot screening, physical examination, and laboratory tests in eight hospitals. The patients were assessed at baseline in terms of their demographic information, medical and social history, peripheral neuropathy disease (PND) screening, periphery artery disease (PAD) screening, assessment of nutritional status, and diabetic control. One year later, the patients were followed up to determine the incidence of new foot ulcers, amputation, and mortality. By univariate analysis, statistically significant differences were found in age, location, gender, living alone (yes/no), occupation, smoking, hypertension, PND, PAD, nephropathy, retinopathy, cataracts, duration of diabetes, Glycosylated hemoglobin A (HbA1c), fasting plasma glucose level, postprandial blood glucose level, insulin level, blood urea nitrogen, creatinine, cholesterol, triglyeride, high density lipoprotein (HDL), serum albumin, white blood cell, and body mass index. A binary logistic regression model was used to examine which of these risk factors were independent risk factors for foot ulceration. A total of 687 (51.5%) of the 1, 333 patients were followed up for an average of 12 months; there were 458 DM patients and 229 DFU patients. A total of 46 patients died during the follow‐up period; 13 were DM patients, and 33 were DFU patients. Of the 641 patients, 445 (69.4%) patients were DM patients, and 196 (30.6%) were DFU patients. At follow‐up, 36/445 DM patients (8.1%), and 62/196 DFU patients (31.6%), developed new ulcers; 10/196 DFU patients underwent an amputation. The annual incidence of ulceration for DM patients and amputation for DFU patients were 8.1 and 5.1%, respectively. The annual mortality of the DM patients and DMF patients were 2.8 and 14.4%, respectively. A binary logistic regression model was used to examine which risk factors were independent risk factors for foot ulceration during the follow‐up period, and the final results showed that nephropathy (odds ratio 2.32), insulin level (odds ratio 3.136, 2.629), and decreased HDL (odds ratio 0.427) were associated with increased risks for foot ulceration. Complications of diabetes affecting the feet represent a serious problem in China. The incidence of foot ulcers and amputation are much higher than that of Western countries. More intensive surveillance and aggressive care following a diagnosis of DFU and earlier referral to specialty care might improve the patient outcome.